2018
DOI: 10.1055/s-0038-1657779
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis and Thrombosis in the Oldest Old

Abstract: There is a growing proportion of the elderly population in the Western world, and these individuals require special considerations regarding a broad variety of aspects, including treatment approaches to illnesses that affect all age groups. The hemostatic system in individuals changes considerably with aging. Specifically, changes in levels of procoagulant and natural anticoagulant factors along with thrombopathy simultaneously create a hypercoagulable state and hemostatic difficulties. Underlying morbidities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Accordingly, thrombosis due to coagulation unbalance or inherited or acquired thrombophilia is a rare event among children [13][14][15][16][17], and this could in part account for the micro-thromboembolic events or cardiac injury found in the elderly severest cases as well the rarer disseminated intravascular coagulation (DIC) [18][19][20], strongly substantiating heparin-based anticoagulant treatments in the selected severe cases [18,21,22]. On the other hand, the severity of COVID-19 worsens with advancing age for both sexes, possibly due to a dysregulation of the immune response, a difference in sex-hormones that has become less evident with age between sexes, or a considerable unbalancing in the coagulation/fibrinolytic system and endothelial dysfunction with aging [23][24][25][26]. Accordingly, in a mouse model, gonadectomy did not affect disease outcome in male mice, whilst ovariectomy or estrogen receptor antagonists caused increased mortality in females after SARS-CoV infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, thrombosis due to coagulation unbalance or inherited or acquired thrombophilia is a rare event among children [13][14][15][16][17], and this could in part account for the micro-thromboembolic events or cardiac injury found in the elderly severest cases as well the rarer disseminated intravascular coagulation (DIC) [18][19][20], strongly substantiating heparin-based anticoagulant treatments in the selected severe cases [18,21,22]. On the other hand, the severity of COVID-19 worsens with advancing age for both sexes, possibly due to a dysregulation of the immune response, a difference in sex-hormones that has become less evident with age between sexes, or a considerable unbalancing in the coagulation/fibrinolytic system and endothelial dysfunction with aging [23][24][25][26]. Accordingly, in a mouse model, gonadectomy did not affect disease outcome in male mice, whilst ovariectomy or estrogen receptor antagonists caused increased mortality in females after SARS-CoV infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Older people are frequently affected by multiple morbidities that are established prothrombotic risk factors, such as congestive heart failure, chronic obstructive disease, diabetes, cancer, chronic venous insufficiency 14 . Advanced age is also associated with an increase of inflammatory state that may be another important stimulus for thrombus formation, but the causal pathways and molecular mechanisms that 15 .…”
Section: Inflammation Thrombosis and Agingmentioning
confidence: 99%
“…With respect to the fibrinolytic system, it has been described a reduction in plasminogen levels in subjects aged 75 years or older 52 , but another study reported that plasminogen levels decreased slightly with age in women but not in men 53 . In contrast, plasminogen activator inhibitor (PAI)-1, which is the major inhibitor of fibrinolysis, increased with advancing age 14 . In particular, PAI-1 is an acute phase reactant influenced by several cytokines, including IL-6, TNF-α, TGF-β and hormones, and its expression is related to stress-induced thrombosis in older people.…”
Section: Changes In Procoagulant Anticoagulant and Fibrinolytic Systmentioning
confidence: 99%
“…55 Indeed, the plasma concentrations of many coagulation factors increase progressively with age, including vWF, factors V, VII, IX, and fibrinogen. 47,56,57 Specifically, the plasma levels of factor VIII can reach higher than 200 U/dl in individuals aged 70 years and over, 58 with an average rise of 5–6 IU/dl per decade. 39,47…”
Section: Reviewmentioning
confidence: 99%
“…This question is particularly pertinent given that a high level of factor VIII is not only a risk factor for the first thrombotic event, but also for recurrent events. 57 Thus, patients identified as having elevated levels may require prolonged anticoagulant treatment to prevent further thrombotic events.…”
Section: Reviewmentioning
confidence: 99%